Context-dependent memory recall in HMD-based immersive virtual environments - Chocholáčková, Mária; Juřík, Vojtěch; Ružičková, Alexandra; Jurkovičová, Lenka; Ugwitz, Pavel; Jelínek, Martin (PloS one, 2023)
The article introduces an original VR-based experiment which explores context-dependent memory recall in humans. It specifically examines the recall of correct and falsely induced semantic memories. With the aid of VR head-mounted displays, 92 students of psychology were placed in a computer-generated indoor virtual environment and asked to memorize the presented lists of words. Afterwards, the participants were placed in the same indoor virtual environment or an alternative outdoor virtual environment and asked to recall the words. The number of correct and falsely induced words was then measured. On average, women recalled significantly more correct words from the list than men, regardless of the environmental context. Despite the assumptions, we did not observe a separate effect of exposure to different environments during learning and recall of material on memory performance. Likewise, we did not detect any effects of the learning context or biological sex in the case of the production of false memories. These results provide a novel insight into previous knowledge regarding the memory processes that occur in virtual environments. Although we failed to confirm the role of context in recalling learned material in general, we found a hint that this context might interact with specific memory processes of biological sexes. However, the design of this study only captured the effect of changing the environment during memory recall and did not address the role of specific context in remembering learning material. Further research is therefore needed to better investigate these phenomena and examine the role of biological sex in context-dependent memory processes.
Keywords: Mental Recall; paměť; kognice; represe (psychologie); mužské pohlaví; ženské pohlaví; Humans; učení; rozpomínání; Cognition; Female; Repression, Psychology; Memory; lidé; Male; Learning